Innovative solutions to tap "Micro, Small and Medium Enterprises" (MSME) market: A way forward for Islamic banks - Muhammad Mohsin Hakeem (Islamic Economic Studies (IES), 2019)
Purpose - The purpose of this paper is to indicate an innovative solution to address the financing issues faced by "Micro-, Small and Medium Enterprises" (MSME) in emerging economies. Design/methodology/approach - Islamic Financial Institutions (IFIs) especially Islamic banks are competing for high net worth individuals, whereas the MSME sector is largely untapped. A collaborative model for IFIs is suggested, to explore the MSME sector. Islamic Non-Banking Financial Institutions (NBFIs) are operating in these markets through their extensive gross route networks. The multistep collaborative model proposes "Special Purpose Entity (SPE)" partially owned by a single Islamic Bank or consortium and NBFI/s. SPEs can be incorporated with a defined scope, focus areas, risk profile, budget and shareholding patterns. Findings - Risk and profit sharing instruments also known as Musharakah and Mudarabah have less than 6 percent share within total financing offered by Islamic banks globally. Risk sharing products offered by Islamic banks are not targeting this sector due to the underdevelopment of instruments, lack of knowledge and resources. Proposed SPEs can operate regionally with a concentration on specific business sectors. Originality/value - The SPE model would enable Islamic banks to enter the huge MSME market while mitigating risk. On the contrary, it would enable the large segments of emerging economies (bottom 40 percent population of developing nations) to get involved and actively play their role to attain long-term development goals.
Keywords: G21; G23; G28; G32; H81; I38; 330; Developing countries; Islamic banking; Economic development; Special purpose entity (SPE); Micro-; small and medium enterprises (MSME); Non-banking financial institutions